Clinicopathological Pattern of Cervical Papanicolaou (PAP) Smears: A hospital based experience - Shrestha, Sujan; Suwal, Ranjan; Gupta, Shyam Nandan (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Cervical cancer is very common type of cancer in women globally. The objective of this study was to compare the cytopathological findings of the cervical pap smears using the revised 2001 Bethesda system and to compare the cytopathological findings with the clinical features. Material and Methods: A total of 1016 pap smear sent to the Department of Cytopathology at Peoples Dental college general hospital (PDCH), Kathmandu over a period of three years were studied. Relevant history and clinical findings were retrieved for the study. The age, caste, location, gravida of the patient, the nature of complaint of patient to the doctor along with the per speculum findings, per vaginal examination findings of the patient and their relation to the cytopathological findings of pap smears were evaluated. Results: No significant relationship was observed between the (30-39 years) aged women and the available outcome of pap smear (p=0.404). Most of the females were Brahmin and Newars. The statistical analysis showed no significant relationship (p>0.05) between the ethnicity and pap smear result. The number of asymptomatic women in this study was found 22.9%. This study found 20.37% of intraepithelial lesion or malignancy. Trichomonas vaginalis and bacterial vaginosis combinely contributed to 0.7% of the total cases in this study. Three smear cases were detected having malignant epithelial cell which were diagnosed with adenocarcinoma, squamous cell carcinoma. Conclusion: In this study cervical pap smear was able to differentiate inflammatory, benign precursors and malignant cases. So, it is desirable to conduct routine Pap smear screening in women of all reproductive age regardless of race, ethnic background and socioeconomic status. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(2): 27-34